Electrochemical Determination of the p53 Tumor Suppressor Gene Using a Gold Nanoparticle-Graphene Nanocomposite Modified Glassy Carbon Electrode. (22nd January 2017) - Feng, Rongrong; Hu, Xiaoqin; He, Caimei; Li, Xiaoxia; Luo, Xianwen
ABSTRACT: A novel sensitive and simple electrochemical DNA sensor is reported for the determination of p53 tumor suppressor gene. A gold nanoparticle/graphene nanocomposite-modified glassy carbon electrode was prepared and methylene blue was used as the hybridization redox indicator. Scanning electron microscopic and electrochemical characterization demonstrated that the gold nanoparticles and graphene were present on the electrode. The resulting sensor provided suitable electrochemical response to the p53 tumor suppressor gene with a linear dynamic range from 0.1 to 1000 nM. The limit of detection was 0.012 nM. The sensor was able to differentiate a complete complementary DNA sequence, single-base mismatched DNA sequence, and a three-base mismatched DNA sequence. The precision of the device was satisfactory, with a relative standard deviation of 4.1% for 11 measurements. The combination of gold nanoparticles and a graphene nanocomposite provided enhanced capabilities for the determination of DNA for clinical applications.